Carboxymethyl cellulose based multifunctional targeted drug delivery platform for pancreatic cancer: nanotheranostic potential and biocompatibility analysis - Joshi, Preeti Nigam; Wangnoo, Shishanka; Louis, Michelle (World Journal of Pharmaceutical Sciences, 2015)

Cells and organs on chip - revolutionary platform for biomedicine - Joshi, Preeti Nigam (Lab-on-a-chip fabrication and application, 2016)

Graphene quantum dot-based on-chip electrochemical DNA hybridization sensor for pancreatic cancer - Joshi, Preeti Nigam; Waghmode, S (Reports in Electrochemistry, 2016)

Graphene quantum dots - from emergence to nanotheranostic applications - Joshi, Preeti Nigam; Kundu, Subir; Sanghi, Sunil K.; Sarkar, Dhiman (Smart Drug Delivery System, 2016)

Green chemistry in nanotechnology: opportunities and future challenges - Joshi, Preeti Nigam (Research and Reviews: Journal of Chemistry, 2016)

Green synthesis of silver nanoparticles from purple acid phosphatase apoenzyme isolated from a new source limonia acidissima - Pawar, Omkar; Deshpande, Neelima; Dagade, Sharda; Waghmode, Shobha; Joshi, Preeti Nigam (Journal of Experimental Nanoscience, 2016)
Green synthesis of nanoparticles is regarded as a safe and non-toxic process whereas conventional synthesis using chemical methods produces toxic substance. This study provides a novel insight for enzymatic synthesis method of silver nanoparticles using purple acid phosphatase, isolated from Limonia acidissima (wood apple) as a new source and used in the synthesis of silver nanoparticles. Stable silver nanoparticles were produced by sonochemical method using apoenzyme as a stabilising and capping agent and were characterised by various physicochemical techniques like UV-Visible spectroscopy, Fourier-transform infrared, X-ray diffraction and transmission electron microscopy. X-ray study shows that nanoparticles are composed of silver and silver oxide. The synthesised nanoparticles exhibited excellent antimicrobial activity against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus.
Keywords: green synthesis; Limonia acidissima; purple acid phosphatase; silver nanoparticles

Multifunctional inulin tethered silver-graphene quantum dots nanotheranostic module for pancreatic cancer therapy - Joshi, Preeti Nigam; Agawane, Sachin; Agawane, Sachin; Agawane, Sachin; Sarkar, Dhiman; Sarkar, Dhiman (Material Science and Engineering C- Materials for Biological Application, 2017)
Cancer nanotechnology is an emerging area of cancer diagnosis and therapy. Although considerable progress has been made for targeted drug delivery systems to deliver anticancer agents to particular site of interest, new nanomaterials are frequently being developed and explored for better drug delivery efficiency. In the present work, we have explored a novel nanoformulation based on silver-graphene quantum dots (Ag-GQDs) nanocomposite for its successful implementation for pancreatic cancer specific drug delivery in wistar rats. Carboxymethyl inulin (CMI); a modified variant of natural polysaccharide inulin is tethered with the nanocomposite via carbodiimide coupling to enhance the biocompatibility of nanoformulation. Experiments are performed to investigate the cytotoxicity reduction of silver nanoparticles after inulin tethering as well as anticancer efficacy of the system using 5-Fluorouracil (5-FU) as model drug. SEM, TEM, FT-IR, UV-vis, photoluminescence and anti proliferative assays (MTT) are performed for characterisation of the nanocomposite. Hyaluronic acid (HA) is conjugated as targeting moiety for CD-44 (cancer stem cell marker) to fabricate a complete targeted drug delivery vehicle specific for pancreatic cancer. In the present work two prime objectives were achieved; mitigation the toxicity of silver nanoparticles by inulin coating and it's in vivo application for pancreatic cancer. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: acid; Dextran; Drug-delivery; graphene quantum dots; Inulin; Nanocomposite; Nanocomposites; Nanoparticles; Pancreatic Cancer; Silver nanoparticle; Strategies; Systems; Targeted Drug Delivery

Synthesis of ecofriendly fluorescent carbon dots and their biomedical and environmental applications - Joshi, Preeti Nigam; Mathias, Anjelica; Mishra, Abhishek (Materials Technology, 2018)
Green Synthesis of nanoparticles is an emerging field with enormous advantages over conventional synthesis methods. Herein we have reported a green method for the preparation of water soluble polydisperse carbon dots (c-dots) from Cocos nucifera frond pinnae by a modified version of the `single step hydrothermal carbonization'. C-dots having blue emission were obtained with this method and we further evaluated the effect of metal ions interactions on c-dots, as a sharp decrease in photoluminescence was observed. The synthesized c-dots were found bioactive against B.subtilis, M. smegmatis and S. aureus as determined by the well diffusion assay. We also explored nanotheranostic applications of c-dots as biosensor matrix in DNA hybridization sensor for pancreatic cancer and in bioimaging of cancer cells. This study demonstrated that c-dots can be explored for numerous biomedical and environmental applications in a variety of fields owing to the cost effective synthesis, biocompatibility and excellent physico-chemical properties.
Keywords: Carbon dots; differential pulse voltammetry; DNA hybridization sensor; green synthesis; Pancreatic Cancer

Rapid and sensitive rGO/AuNP-based electrochemical nano-biosensor for detection of E. coli and S. aureus in less than an hour - Sirdeshmukh, Vedashree V.; Joglekar, Shreeram S.; Joshi, Preeti Nigam; Kale, Anup A. (AIP Advances, 2025)
Improved diagnostic screening has become critical for bacterial infection identification and prevention. The sensitivity, reliability, repeatability, detection time, and specificity of a test or tool are critical for its translation to application. Electrochemical detection methods are quick and can provide point-of-care diagnosis. We report on reduced graphene oxide/gold (rGO-AuNP) nanocomposites that enabled highly sensitive and quick detection of harmful bacteria, such as E. coli and S. aureus. The technique involved employing rGO as a nano-carrier and Au as a bioactive surface to bind particular antibodies for electrochemical immunoassays. The current approach is culture-independent and does not require sample processing for bacterial detection. It is a pathogen detection technology that uses rGO-AuNP as an electrochemical transducer platform and target particular antibodies for E. coli and S. aureus to obtain improved sensitivity and speed. Differential pulse voltammetry was used to detect infections. These findings demonstrated that rGO-AuNp nanocomposites have up to three times the sensitivity of rGO and AuNP alone. Importantly, the antibody linked bioactive screen-printed electrodes remained stable for more than a month, allowing just electrochemical measurements to be performed at the time of detection. This allowed for pathogen detection in less than an hour. The limit of detection for both E. coli and S. aureus was 2 CFU/ml, making it extremely sensitive. An electrochemical sensor was showing a linear response with R2 0.98. According to the physicochemical evaluation of nanocomposites, the improved sensitivity and stability were caused by a lowered bandgap in composites and uniform distribution of AuNPs on a rGO nano-template. (c) 2025 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution-NonCommercial-NoDerivs 4.0 International (CC BY-NC-ND) license (https://creativecommons.org/licenses/by-nc-nd/4.0/).